Comparing the influence of regularly prescribed pharmaceuticals on the chemotactic effects of autologous blood clots in the context of diabetic wounds - Armstrong, Kayleigh Ann (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.